Root‐cause analyses of missed opportunities for the diagnosis of colorectal cancer in patients with inflammatory bowel disease. Issue 2 (7th November 2020) - Gordon, Claire; Chee, Desmond; Hamilton, Ben; Heerasing, Neel M.; Hendy, Peter; Chanchlani, Neil; Lin, Simeng; Wesley, Emma; Daniels, Ian R.; Silva, Nishanthi; Osborne, Melanie; Kennedy, Nicholas A.; et al.
Summary: Background: Colonoscopic surveillance in patients with inflammatory bowel disease (IBD) leads to earlier detection of colorectal cancer (CRC) and reduces CRC‐associated mortality. However, it is limited by poor adherence in practice. Aim: To identify missed opportunities to detect IBD‐associated CRC at our hospital Methods: We undertook root‐cause analyses to identify patients with missed opportunities to diagnose IBD‐associated CRC. We matched patients with IBD‐associated CRC to patients with CRC in the general population to identify differences in staging at diagnosis and clinical outcomes. Results: Compared with the general population, patients with IBD were at increased risk of developing CRC (odds ratio 2.7 [95% CI 1.6‐3.9], P < 0.001). The mean incidence of IBD‐associated CRC between 1998 and 2019 was 165.4 (IQR 130.4‐199.4) per 100 000 patients and has not changed over the last 20 years. Seventy‐eight patients had IBD‐associated CRC. Forty‐two (54%) patients were eligible for CRC surveillance: 12% (5/42) and 10% (4/42) patients were diagnosed with CRC at an appropriately timed or overdue surveillance colonoscopy, respectively. Interval cancers occurred in 14% (6/42) of patients; 64% (27/42) of patients had a missed opportunity for colonoscopic surveillance where root‐cause analyses demonstrated that 10/27 (37%) patients known to secondary care had not been offered surveillance. Four (15%) patients had a delayed diagnosis of CRC due to failure to account for previous colonoscopic findings. Seventeen (63%) patients were managed by primary care including seven patients discharged from secondary care without a surveillance plan. Matched case‐control analysis did not show significant differences in cancer staging or 10‐year survival outcomes. Conclusion: The incidence of IBD‐associated CRC has remained static. Two‐thirds of patients eligible for colonoscopic surveillance had missed opportunities to diagnose CRC. Surveillance programmes without comprehensive and fully integrated recall systems across primary and secondary care are set to fail.